Leader Member Exchange (LMX) on Turnover Intention with Job Satisfaction as a Mediating Variable - Yolanda Oktaviani; Yuki Fitria (Universitas Negeri Padang, 2021)
The purpose of this study was to examine: (1) The effect of leader member exchange on turnover intention. (2) The effect of leader member exchange on job satisfaction. (3) The effect of job satisfaction on turnover intention. (4) The effect of leader member exchange on turnover intention through job satisfaction. The population in this study were all RST contract nurses. DR. Reksodiwiryo Padang totaling 152 people using proportional cluster random sampling. The analytical technique used is SEM analysis using smart PLS3. The results of this study indicate that: (1) leader member exchange has a negative and significant effect on turnover intention. (2) leader member exchange has a positive and significant effect on job satisfaction. (3) job satisfaction has a negative and significant effect on turnover intention. (4) Leader member exchange has a significant effect on turnover intention with job satisfaction as a mediating variable.